Aquinas after Joyce: Thomist aesthetics in light of contemporary art - Funk-Deckard, Michael (Verbum – Analecta Neolatina, 2005)
According to the Irish novelist James Joyce, Thomas Aquinas’s well-known formal trilogy from the Summa Theologiae is central to understanding beauty: proportio, claritas, and integritas. Joyce in fact formulated a youthful aesthetic based on Aquinas in his novel, A Portrait of the Artist as a Young Man (1916). Despite Joyce’s ontological misunderstanding of Thomas, this article resumes several interpretations of Thomist aesthetics (i.e., J. Maritain, U. Ecco, and F. J. Kovach) and strives to renew an understanding of contemporary art with regard to its relationship to the good/true and the possible rejection of this relationship.